STRATEGI PEMBELAJARAN MURDER UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS X PADA MATERI PAI DI SMK TI BAHRUL ULUM JOMBANG - Emi Lilawati; M Alvian Eko F; M Aliyul Wafa (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
The research objectives to be achieved in this study are (1) to find out or implement a MURDER strategy to improve students' understanding of PAI material at SMK TI Bahrul Ulum Jombang . (2) To find out the mastery of students' understanding of PAI material at SMK TI Bahrul Ulum Jombang through the application of MURDER learning strategies. Which is based on the formulation of the problem, namely (1) How to implement the MURDER strategy to improve students' understanding of the PAI material at SMK TI Bahrul Ulum Jombang (2) How to master the MURDER strategy to improve students' understanding of PAI material at SMK TI Bahrul Ulum Jombang To achieve the above objectives, the researchers used qualitative research types . This research uses a descriptive approach and data collection by researchers in the form of observation methods, interview methods, and documentation methods. Then the technical analysis of data used by researchers is using data reduction, data presentation, and data withdrawal.rom the results of data analysis regarding the Murder learning strategy to increase students' understanding of PAI material at SMK TI Bahrul Ulum Jombang, namely: Learn to be confident in expressing opinions. While the shortcomings are difficult to condition students. However, the teacher has been able to create students with patience to teach and the teacher tries to motivate students to be more enthusiastic about learning. Keywords: MURDER Strategy, Understanding, Qualitative